Filsafat Idealisme: Implikasinya dalam Pendidikan - Rusdi, Rusdi (Dinamika Ilmu, 2013)
Idealism is a philosophy that holds that the world of ideas and the idea is the nature of reality. Reality is not actually present in the material object, but there are in the minds of the idea. Although idealism considers that the essence is the idea. He continued to recognize the existence of matter. But according to him, the main thing is the world of ideas because the first idea existed before matter. This philosophy, then give implications for education. The philosophy of the building forming an understanding that education is constructed based on the ideas that emphasizes abstract reasoning and moral.